The Relationship Between Initial Understanding of Flat Builds and the Ability to Determine the Height of a Triangle - Rafi Muhammad, Alifiandi; Irawati, Santi; Suliantoro, Tamyis (Universitas Negeri Malang, 2023)
This study explores how students' understanding of plane figures relates to their ability to determine triangle altitudes at the junior high school level. Understanding altitude determination is crucial for various math tasks. The aim is to gauge how students' initial understanding influences their ability to apply altitude concepts in math learning at the junior high school level. Data were collected from 28 eighth-grade students through a preliminary ability test (PAT) and non-routine challenge questions to determine the altitudes of right and obtuse triangles. Descriptive analysis, cross-tabulation, and chi-square tests were conducted to assess the relationship between students' initial abilities in plane figures and their ability to determine triangle altitudes. The chi-square test results show that there is no significant relationship between students' initial abilities and skills in solving PAT questions and their ability to determine the altitudes of right-angled or obtuse triangles. These findings suggest that the ability to answer PAT questions does not always mean meaning only sometimes means the ability to solve problems related to applying these concepts.